FORMATION OF READING AND WRITING SKILLS IN THE EDUCATIONAL AND PROFESSIONAL SPHERE - Elmuradova L.N; Shomurotova O.X (Western European Studies, 2024)
The study reveals the specifics of a multimodal approach to the formation of professional skills of teachers as a basis for teaching reading and writing skills. The writing process is much more intense and complex than oral speech, proceeds more consciously and requires the writer to focus maximum attention on the content and on the ways of expressing thoughts. In adults, motor control plays an important role in controlling the writing process and in preventing violations of graphic forms, while in student, motor complexes are poorly developed and uncertain at the beginning of learning.
Keywords: Writing; reading; skill; pedagogic skill